Improved Hydrogen Production Through Electrochemical Dehydrogenation of Tetrahydroquinolines Using TEMPO to Suppress Dimerization - Choo, Aeri; Cheong, Jaehwan; Kim, Yongmin; Jeong, Hyangsoo; Kim, Joohoon (John Wiley & Sons Inc., 2025)
As a sustainable and effective strategy for hydrogen production, the electrochemical dehydrogenation of saturated organic heterocycles has recently gained significant attention in energy research. Here, we present an unusual perspective on the electrochemical dehydrogenation of 1,2,3,4-tetrahydroquinoline (THQ) and its derivatives, for example, 2-methyl-1,2,3,4-tetrahydroquinoline (M-THQ), in the presence of (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) in acetonitrile. The electrochemical oxidation of THQs led to their dimerization, thereby restricting the efficient electrochemical dehydrogenation of THQs. Detailed electrochemical studies revealed the crucial role of TEMPO in suppressing the side reaction of dimerization, consequently enhancing the electrochemical dehydrogenation of THQs when TEMPO is employed.